Ulasan Ilmiah: Hubungan Resiko Keamanan Pangan dan Kepercayaan Konsumen dalam Rantai Pasok Produk Susu - Alnadia Yusriya Hibatullah; Lillah Asritafriha; Syadza Hanifah (Universitas Bumigora, 2023)
In 2019 and 2020, the condition of the food safety system in Indonesia was still relatively low. This was showed by the rise in food safety incidents, one of which is in dairy products. The incidents that occurred had led to reduced consumer confidence in the quality and safety of dairy products, even though these products provide an important source of nutrition for growing children. The benefits of milk can be optimally obtained by maintaining food safety standards and ensuring that dairy products are tested as healthy for consumers. Therefore, this article aims to discuss the relation between food safety risk and consumer confidence in the dairy product supply chain as well as future perspectives that can be adopted by the industry to increase consumer confidence in the dairy product supply chain. This research paper investigates by literature review. The findings reveal that ensuring the safety of dairy products are the strategy to establish and maintain consumer trust. The consumer trust can be achieved when operators, distributors, and food vendors consistently deliver a safe product with relevant standards. To enhance consumer trust can be done by reforming and improving the quality assurance of products certified by authorized regulatory bodies and establishing traceability of the food supply chain. Emerging trends that are expected to revolutionize the food industry include transparency, sustainability, and health-oriented approaches, with blockchain technology being one of the promising solutions.